2014
DOI: 10.5152/tjbh.2014.1675
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like Carcinoma of the Breast: A Case Report

Abstract: Lymphoepithelioma-like carcinoma carries similar histopathological features with lymphoepithelioma typically located in the nasopharynx. Lymphoepithelioma-like carcinoma of the breast can be mistaken for breast lymphoma or medullary carcinoma due to the undifferentiated appearance of tumor cells and presence of prominent lymphoid component. Lymphoepithelioma-like carcinoma is rare, and the similarity between medullary carcinoma of the breast makes it difficult to distinguish these two tumors. In the presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The clinical characteristics of the previous reports are summarised in Table I. Morphologically, tumour necroses were identified in two patients in the Dadmanesh series as well as in five more cases [5,10,15,19,24]. A lobular variant of LELC-B has been reported by some authors [3,4,7,9] associated with LCIS [3,4,7], pagetoid spread [4], or with atypical lobular hyperplasia [9].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The clinical characteristics of the previous reports are summarised in Table I. Morphologically, tumour necroses were identified in two patients in the Dadmanesh series as well as in five more cases [5,10,15,19,24]. A lobular variant of LELC-B has been reported by some authors [3,4,7,9] associated with LCIS [3,4,7], pagetoid spread [4], or with atypical lobular hyperplasia [9].…”
Section: Discussionmentioning
confidence: 97%
“…Ductal carcinoma in situ was not identified in any of the previous cases. In three of the cases there was association with sclerosing lymphocytic lobulitis in the surrounding breast parenchyma [6,19,20]. Kurose et al reported glandular differentiation on electron microscopy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoepithelioma-like carcinoma (LELC) is a relatively rare type of nonkeratinizing carcinoma characterized by prominent infiltration of lymphocytes. Although it primarily originates from the nasopharynx, rare cases occurring in other organs (e.g., the liver, breast, bladder, cervix, and lung) have also been previously reported [1][2][3][4][5] . Primary LELC of the lung was first described by Bégin et al [6] in 1987.…”
Section: Introductionmentioning
confidence: 99%